(untitled) (Research, Society and Development, 2022)
This study aimed to analyze attitudinal and structural aspects of inclusion of People with Disabilities (PwD’s) in bodybuilding academies. The sample consisted of 95 participants, involving Physical Education Professionals, interns and gym owners. The instruments used were a questionnaire and observation form according to the criteria of (NBR 9050/2015). The participants considered that there was a flaw in the attitudinal aspect of inclusion, since they considered themselves “not prepared” or “little prepared” to work with PwD’s and that improvements in architectural accessibility were necessary in the establishments where they work. It is concluded that both in an attitudinal and structural way, the fitness centers are deficient inclusion environments.